Emerging diseases of goats in Malaysia - Mohamed Mustapha, Noordin; Koran, Ragavan; Shamsudin, Shahirudin; Goriman Khan, Mohd Azam Khan; Allaudin, Zeenathul Nazariah; Arshad, Aziz; Awang Isa, Kamarudin (Universiti Putra Malaysia Press, 2010)
Malaysia is aggressively reviving its sluggish small ruminant industry via imports of high and good quality productive goats. However, certain diseases especially the ones which take an insidious course may be missed (rather long incubation period) during quarantine. This paper describes the first definite outbreak of caprine arthritis encephalitis (CAE) and coenuriasis in goats. The disease was confirmed via clinical signs, pathology, and virus isolation (CAE). Further corrective and preventive measures are being discussed.